2010
DOI: 10.22230/jripe.2010v1n3a25
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Workplace Factors Influencing Expertise in the Delivery of Children’s Education and Mental Health Services

Abstract: Background: Interest in professional expertise is growing. Interactional and developmental perspectives are being adopted to understand the nature of expertise and the environmental factors that influence its development. This article provides qualitative information about the workplace factors and experiences considered important by individuals providing education or mental health services to children, with one group working within an interprofessional team approach (service providers) and the other working i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…The cornerstone of this course's curriculum was rooted in inclusive education, with a stance that all students belong and are part of the community (King et al, 2010). Most students with identified exceptionalities, including mental illness, spend considerable time in a regular classroom.…”
Section: Learning Objective #3mentioning
confidence: 99%
“…The cornerstone of this course's curriculum was rooted in inclusive education, with a stance that all students belong and are part of the community (King et al, 2010). Most students with identified exceptionalities, including mental illness, spend considerable time in a regular classroom.…”
Section: Learning Objective #3mentioning
confidence: 99%
“…As described in our article examining workplace factors influencing expertise development (King et al 2010), therapists and teachers took part in separate focus groups in order to facilitate focused discussion of expertise in their profession. The semi-structured focus groups were facilitated by two study investigators using a standard protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Practitioners' tacit knowledge was made visible by examining story narratives emerging in the context of group discussion (Soubhi et al 2009). A previous article based on this study examined workplace factors influencing expertise in the delivery of children's education and mental health services (King et al 2010). This previous article pointed to the importance of relationship-oriented and collaborative service delivery models, and indicated that workplace settings should provide natural learning opportunities involving interaction, dialogue and feedback.…”
Section: Interprofessional Comparisons Of Changes In Perspective and mentioning
confidence: 99%
“…Acquiring practical experience in local schools is a key component of the development of preservice teachers' inclusive instruction, beliefs and confidence (Voss & Bufkin, 2011). However, little is known about the specific nature of experiences that preservice teachers identify as important aspects of their development as inclusive teachers (King et al, 2010). In a study of inservice teachers and school leaders, Howell (2017) found that both groups valued leaders' behaviors which support teamwork and collaboration for inclusive instruction.…”
Section: Perspective(s) or Theoretical Frameworkmentioning
confidence: 99%